2010
DOI: 10.3233/ves-2010-0344
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating ascending vestibular pathways to the cortex involved in spatial cognition

Abstract: Vestibular information is an important factor in maintaining accurate spatial awareness. Yet, each of the cortical areas involved in processing vestibular information has unique functionality. Further, the anatomical pathways that provide vestibular input for cognitive processes are also distinct. This review outlines some of the current understanding of vestibular pathways contributing to the perception of self-motion in the cortex. The vestibulo-thalamic pathway is associated with self-motion cues for updati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 262 publications
1
68
0
5
Order By: Relevance
“…The premotor cortex, motor cortex, supplementary eye fields, and frontal eye fields, all areas with known vestibular responses (Fukushima et al, 2000, Fukushima et al, 2004a, Fukushima et al, 2004b, Fukushima et al, 2006, Shinder and Taube, 2010, Fukushima et al, 2011), project to the PPN (Stanton et al, 1988a, Matsumura et al, 2000). The supplementary and frontal eye fields also project to the cMRF (Huerta and Kaas, 1990, Shook et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The premotor cortex, motor cortex, supplementary eye fields, and frontal eye fields, all areas with known vestibular responses (Fukushima et al, 2000, Fukushima et al, 2004a, Fukushima et al, 2004b, Fukushima et al, 2006, Shinder and Taube, 2010, Fukushima et al, 2011), project to the PPN (Stanton et al, 1988a, Matsumura et al, 2000). The supplementary and frontal eye fields also project to the cMRF (Huerta and Kaas, 1990, Shook et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is certain to be one important relay station for the transmission of at least some ascending vestibular information. However, the number of different vestibulo-hippocampal pathways and their precise nature, remains to be determined (Smith, 1997; see Shinder and Taube, 2010 and Hufner et al, 2011 for recent reviews). It must also be kept in mind that the hippocampus is only one part of a highly complex system of limbic-neocortical pathways that are responsible for spatial memory (Guldin and Grusser, 1998; Hanes and McCollum, 2006; Gu et al, 2007; Shinder and Taube, 2010; Lopez and Blanke, 2011).…”
Section: Effects Of Vestibular Lesions On Head Direction Cell and Plamentioning
confidence: 99%
“…However, the number of different vestibulo-hippocampal pathways and their precise nature, remains to be determined (Smith, 1997; see Shinder and Taube, 2010 and Hufner et al, 2011 for recent reviews). It must also be kept in mind that the hippocampus is only one part of a highly complex system of limbic-neocortical pathways that are responsible for spatial memory (Guldin and Grusser, 1998; Hanes and McCollum, 2006; Gu et al, 2007; Shinder and Taube, 2010; Lopez and Blanke, 2011). In humans, fMRI has revealed that areas of significant activation by galvanic vestibular stimulation (GVS) include the posterior insula, the retroinsular regions, the superior temporal gyrus, parts of the inferior parietal lobule, the intraparietal sulcus, the post-central and pre-central gyrus, the anterior insular, the inferior frontal gyrus, the anterior cingulate gyrus, the precuneus and the hippocampus (Lobel et al, 1998; see Karnath and Dieterich, 2006 for a review).…”
Section: Effects Of Vestibular Lesions On Head Direction Cell and Plamentioning
confidence: 99%
“…Furthermore, the spatially related modulation of activity of neurons believed to be critical for spatial cognition, including place cells in the hippocampus (Russell et al, 2003b) and head direction cells in the lateral mammillary nucleus, postsubiculum, and anterior thalamic nuclei (Stackman and Taube, 1997; Taube, 1998; Muir et al, 2009; Shinder and Taube, 2010), is lost following bilateral vestibular lesions. The effects of removal of labyrinthine inputs on navigational abilities showed little recovery even when animals were tested 14 months after injury (Baek et al, 2010).…”
Section: Compensation Following Bilateral Vestibular Dysfunction: Stumentioning
confidence: 99%
“…As illustrated in Figure 4, one difference between the deficits that dissipate and those that do not is the region of the vestibular nucleus complex where they are mediated. Vestibulo-ocular reflexes are mainly elicited by neurons in the rostral portion of the vestibular nucleus complex (Graybiel and Hartwieg, 1974; Gacek, 1977, 1979a,b), as are cognitive responses that are dependent on labyrinthine inputs (Brown et al, 2005; Shinder and Taube, 2010). In contrast, many of the neurons that control balance (Nyberg-Hansen and Mascitti, 1964; Petras, 1967; Peterson et al, 1978; Carleton and Carpenter, 1983; Carpenter, 1988) and influence blood pressure (Uchino et al, 1970; Yates et al, 1993; Kerman and Yates, 1998) are located caudally in the vestibular nucleus complex.…”
Section: Compensation Following Bilateral Vestibular Dysfunction: Stumentioning
confidence: 99%